(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Women entrepreneurs play a critical role in the globalised world, and they have becomeing an indispensable component of the worldwide search for sustainable financial growth and social progress. Women’s entrepreneurship is a comparatively new phenomena. Women-owned businesses are rapidly developing in practically all economies as a result of increased industrialization, social laws, urbanisation, political and economic developments. Women’s roles have evolved from the kitchen to higher levels of professional activity as a result of increased education and awareness. In India, women’s entrepreneurship is gaining traction. Women are increasingly becoming entrepreneurs in modern India, particularly in MSMEs. Women entrepreneurs, on the other hand, confront a slew of societal, economic, and familial issues. This article focuses on the challenges that women entrepreneurs confront in today’s competitive business climate.